The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2325967118814238
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Concussions in Major League Baseball: A Historical Cohort Study of Return to Play, Performance, Longevity, and Financial Impact

Abstract: Background:The short-term outcomes of concussions within Major League Baseball (MLB) warrant further consideration beyond a medical standpoint given that performance, career, and financial data remain unknown. The perception of this injury directly affects decision making from the perspective of both player and franchise.Purpose:To evaluate the effect of concussion on MLB players by (1) establishing return-to-play (RTP) time after concussion; (2) comparing the career length and performance of players with conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
3
19
1
Order By: Relevance
“…In another study examining the effects of concussion among professional baseball players, Ramkumar et al 36 found that batters had a significant decrease in BA and OBP postconcussion, both before and after 2011. These findings are in keeping with the current study, which also demonstrated a significant drop in sabermetric performance measures such as wOBA, wRC+, and WAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study examining the effects of concussion among professional baseball players, Ramkumar et al 36 found that batters had a significant decrease in BA and OBP postconcussion, both before and after 2011. These findings are in keeping with the current study, which also demonstrated a significant drop in sabermetric performance measures such as wOBA, wRC+, and WAR.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although there was no control group of players with alternate injuries or returning from nonmedical leave to compare performance measures, the current study used each player's preconcussion performance as an internal control to evaluate the impact of concussion. 9,36 Future research needs to be done with access to medical charts to identify players with concussions and specify mechanism of injury. Comparisons should be made with a control group of players with alternate injuries or returning from nonmedical leave to better determine the effects of concussion on performance both in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigations in recent years have examined concussive injuries in the NFL, 6,9,22,37 NHL, 11,26,27 and MLB. 5,48,50,53 In each of these professional leagues, authors have reported that the institution of league-wide, formalized concussion policies resulted in increases in concussion incidence. 26,37,50 However, in one of the relatively few investigations that has studied concussions in NBA players, Padaki et al 45 found that incidence was not statistically different following the institution of the NBACP but that RTP time had increased.…”
mentioning
confidence: 99%
“…In baseball, where increased research into pitching biomechanics, quantitative performance analytics, and pitch counts highlights the growing concern for injury awareness and proclivity, there exists little evidence on the epidemiology and effects of predraft injuries in MLB. 8,20 In a recent comprehensive review of major and minor league baseball injury epidemiology, Camp et al 3 described the limitations of unofficial, publicly available data as follows: low fidelity with absent medical specialist oversight, low granularity of diagnoses and pathoanatomy, and misinterpretation commonly attributed to the reliance on roster management tools such as the disabled list (DL).…”
mentioning
confidence: 99%